The Fundamental Doctrines of Imami Shi’a, Other Shi‘a Sects (Zaidiyah, Isma’iliyah and Gulat), and Their Doctrinal Teachings - Nuha, Ken Ulin; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research discusses Shia: The Fundamentals of Shia Imamiyah Teachings, Other Shia Sects such as Zaidiyah, Isma’iliyah, and Gulat, as well as their teachings. The objectives of this research are: To understand the concept of the Shia sect and the history of its emergence; to understand the fundamental teachings of the Itsna Ashariyah or Shia Imamiyah sect; and to understand and comprehend the other Shia sects and the concepts of their teachings. The author employs qualitative research, which serves as a method to obtain descriptive data in the form of written or oral expressions from individuals or through observation of behavior. The purpose of this research is to describe the views of Maturidiyya along with its teachings. Therefore, this paper is compiled through a literature review. To collect data, the author utilizes libraries, by analyzing various literatures relevant to the topic discussed, both in Indonesian and foreign languages. In addition, the sources of this research also include primary data. The research results indicate that the Shia group is a faction of supporters/followers of Ahl al-Bayt who later disguised themselves as supporters of Ali, believing that the caliphate is the right of Ahl al-Bayt (Ali and his descendants) due to their virtue and nobility. The Shia group initially emerged after the death of the Prophet Muhammad (peace be upon him) and the appointment of Abu Bakr as the successor caliph. However, according to historians, this group politically appeared during the Battle of Siffin between Ali and Mu’awiyah. The Imamiyah or Ja'fariyah or Ithna Ashariyah sect of Shia is the largest Shia sect and is considered the closest to the Sunni community, possessing the concept of Usul al-Din oriented towards five aspects, namely: (1) Tawhid, (2) Al-Adl, (3) Nubuwwah, (4) Ma’ad, and (5) Imamah. There are differences of opinion among several scholars regarding the number of Shia sects. However, in this paper, the author mentions the sects that are quite influential and have distinct characteristics in their views on the concept of imamah. These sects are (1) Zaidiyah, (2) Isma’iliyah, and (3) Ghullat (extremist), aside from the Itsna Ashariyah group mentioned earlier.